Inducing the Health Promotion Model for Nursing Practice: Qualitative Study - Khalifa, mohammed; Abdul-Wahid, hala (Iraqi National Journal of Nursing Specialties, 2006)
Objective: To generate a model that conceptualizes the phenomenon of health promotion and its related factors.Methodology: A grounded theory methodology is used as qualitative method to explore the health promotion asphenomenon of interest and its other related factors from the perspectives of specialists in this field. The study iscarried out from January 2002 through September 2004. A sample of (20) specialists in health sciences areselected and interviewed as experts in the area of health promotion. The investigators conducted intensive andstructured interviews with the specialists to collect the data. These interviews were transcribed verbatim,analyzed and interpreted.Results: Findings of the study indicated that health promotion is affected by multiple factors including humanones (i.e., health balance, attitudes, health potentials, environmental or ecological factors, social and culturalfactors). From the model, numerous nursing interventions can be drawn for assessment, implementation andevaluation that may assist to maintain and improve health, as well as achieve optimum level of health.Recommendations: The study recommends that further research can be conducted to examine this model for itscompatibility and applicability for nursing practice in the area of health promotion.